Looking Also from Another Perspective: Exploring the Benefits of Alternative Views for Alignment Tasks - Martin-Gomez, Alejandro; Eck, Ulrich; Fotouhi, Javad; Navab, Nassir (Proceedings - 2020 IEEE Conference on Virtual Reality and 3D User Interfaces, VRW 2020, 2020)
Object alignment is an activity frequently performed in several domains. Traditional AR/VR methods provide virtual guides such as text, arrows, or animations to assist users during alignment. This work explores the feasibility of using virtual cameras and mirrors instead. We conducted a study where participants aligned objects assisted by virtual cameras and mirrors in VR. Data regarding alignment, time to completion, users' distance traveled, average head velocity, usability, and mental effort was collected. Results show that virtual helpers reduce mental effort and distance traveled and increase acceptance without negatively affecting alignment accuracy.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Human-centered computing [Human computer interaction (HCI)]: HCI design and evaluation methods; Human-centered computing [Human computer interaction (HCI)]: Interaction paradigms; Human-centered computing [Visualization]: Visualization design and evaluation methods; User studies; Virtual reality